Formulasi dan Evaluasi Sifat Fisik Granul Effervescent Vitamin C dengan Metode Granulasi Kering - Aulia Jihan Kamila; Hasna Nisrina Huwaida Isfaizah; Nadia Afianti Nugraha; Muqsidana Sayidina Gara Putra; Aurelia Devi Ramadhani (Lembaga Pengembangan Kinerja Dosen, 2026)
Effervescent granules are a pharmaceutical dosage form that offer advantages in terms of ease of use, improved palatability, and rapid solubility in water. This study aimed to formulate and evaluate the physical properties of vitamin C Effervescent granules using the dry granulation method. The main materials used included ascorbic acid as the active substance, citric acid and tartaric acid as acid sources, and sodium bicarbonate as the base source. Evaluation was carried out on organoleptic properties, flow properties, pH, angle of repose, moisture content, density, compressibility index, and dispersion time. The results showed that the granules met the requirements for organoleptic properties, pH (4–5), angle of repose (38.41°), compressibility index (12.3%), and dissolution time (49.62 seconds). However, the flow property (29.11 seconds) and moisture content (6.47%) did not meet the established standards. These findings indicate that the formulated granules met most of the evaluation parameters but still require optimization, particularly in the drying process and flow properties, to obtain a more stable and high-quality dosage form.